(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The efficiency of the tax system is measured in the efficiency of the standard bases for collection of tax revenues and not on the contraction imposed taxes, As using cash basis which is based on measuring what was collected in the fiscal year is not taxed and not what was estimated by the taxpayers, The methods of collection different from country to country and from one to another depending on the nature of taxable income,and the timing of tax collection, the tax administration shall determine the appropriate dates for collection of the tax and shall follow certain collection methods, The problem of research is reflected in the low relative importance of tax revenues in the state budget as a result its ineffective contribution to the achievement of various economic and social goalsd ifferent, The matter, Which places additional responsibilities on tax policy makers in order to activate its contribution in the face of the political, economic and social conditions, The research aims is to study the effect of changes in some factors related to tax and tax administration and legislative factors on the collection of revenues in Iraq for the period (2003-2015) using some statistical methods, including measures of central tendency and simple linear correlation and multiple, and the interpretation of changes in the tax revenue, The research was based on the method of analyzing the tax revenue data to explain the results obtained by the Ministry of Finance, the general commission for Taxes and the Central Statistical organization, The research found that the income tax constituted the highest relative importance of total direct tax revenues This is due to the fact that income taxes are characterized of exemptions and permits that have a significant impact on the tax revenues, on the contrary,land tax which is a relatively less important of direct revenues and no hold any appropriate adjustments have been made to its tax price, The research recommends that the need to balance of the tax structure in Iraq through direct and indirect taxes,and reducing the discrepancy as much as possible, review the price of land tax and increasing the tax rate commensurate with the public value of the bid in order to contribute to the increase in tax revenues.